DESIGNING A PROTOTYPE OF MATHEMATICS LEARNING MEDIA BASED ON AUGMENTED REALITY INTEGRATED WITH PROBLEM BASED LEARNING IN AN ETHNOMATHEMATICS CONTEXT - Arvangga Oktadian Krisbiyantoro; Puji Lestari (Universitas Negeri Semarang, 2025)
Mathematics learning in Indonesian elementary schools faces persistent challenges, particularly in geometry, where students struggle to recognize plane figure properties and apply concepts to real-life contexts. These difficulties stem from teacher-centered instruction and static media that offer limited interactivity and contextual relevance, leading to low motivation and weak conceptual understanding. Augmented Reality (AR) can address this through interactive visualization of geometric objects, while Problem Based Learning (PBL) provides a collaborative, authentic problem-solving framework. Integrating both with ethnomathematics which links mathematics to local culture can enhance engagement and meaningfulness. This study aims to design a conceptual prototype of AR-based mathematics learning media integrated with PBL in an ethnomathematics context for Grade V plane geometry (squares, rectangles, triangles, and circles). A qualitative descriptive method was employed through needs, curriculum, and concept analyses based on literature and Merdeka Curriculum documents. Findings reveal that existing media lack integration of interactive technology, contextual problem-solving, and cultural relevance. Consequently, a conceptual prototype named ETMAR (Ethnomathematics Augmented Reality) was designed as a web-based platform accessible on laptops and mobile devices. It features interactive 3D model visualization on laptops and AR visualization on mobile devices, contextualizing Semarang's historical landmarks Lawang Sewu, Tugu Muda, and Gereja Blenduk as ethnomathematics contexts within PBL-based problem scenarios for plane geometry. This prototype provides a theoretically grounded foundation for future development, expert validation, and classroom implementation.